1992
DOI: 10.1021/ic00045a010
|View full text |Cite
|
Sign up to set email alerts
|

Organotransition-metal metallacarboranes. 29. Synthesis of selectively C- and B-substituted double- and triple-decker sandwiches. (.eta.5-C5Me5)CoIII(.eta.5-R2C2B3R'3H2) cobaltocenium analogs

Abstract: In earlier publications from our laboratory, methods were described for the regiospecific introduction of organic substituents onto cage boron and carbon atoms in small metallacarborane clusters. Here we report the selective application of these approaches in the targeted synthesis of several double-decker, triple-decker, and tetradecker sandwich compounds including the parent species ( C S M~~) C O ( C~B~H~) and ( C S M~~) C~( C~B~H S ) C O ( C~M~S ) . The peralkyl species (C5Me5)Co11'[(Me2C2B3Me3(p-H)2] (51,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…145 Most recently, a number of C-and B-substituted doubleand triple-decker sandwich complexes of Co have been prepared and thoroughly characterized. 146 Initially, the precursor, Cp*Co(Me2C2B4H4), was converted to the corresponding B-Me-substituted species, Cp*Co(Me2C2B3Me3H2), in a number of steps involving decapitation by wet TMEDA and repeated deprotonations with butyllithium, followed by the reactions with methyl iodide. The crystal structure revealed that this intermediate complex is a decapitated mixed-ligand and staggered sandwich as in (Cp*2Co)+.…”
Section: Llnked-cage and Multidecker Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…145 Most recently, a number of C-and B-substituted doubleand triple-decker sandwich complexes of Co have been prepared and thoroughly characterized. 146 Initially, the precursor, Cp*Co(Me2C2B4H4), was converted to the corresponding B-Me-substituted species, Cp*Co(Me2C2B3Me3H2), in a number of steps involving decapitation by wet TMEDA and repeated deprotonations with butyllithium, followed by the reactions with methyl iodide. The crystal structure revealed that this intermediate complex is a decapitated mixed-ligand and staggered sandwich as in (Cp*2Co)+.…”
Section: Llnked-cage and Multidecker Complexesmentioning
confidence: 99%
“…147 The shorter metal to carborane ring centroid distance, compared to that in the metallocene analogue (1.54 A vs. 1.68 A), demonstrates the stronger bonding capability of the carborane ligand than the cyclopentadienide as previously demonstrated.8 The synthetic utility of this complex as well as the corresponding C(Cage)-H or -SiMe3-substituted analogues has been demonstrated further in the preparation of a number of triple-decker sandwiches, [Cp*Co(R,R,-C2B3R//3)Cp*Co](R,R/,R" = H, Me, or SiMe3). 146 The results to date indicate that the area of linked cage and multidecker sandwich complexes is still in its developing stage, and more advanced research needs to be done to find their applications, in an absolutely practical sense, as new materials in electronic industries. Nonetheless, the above results give every indication that this area of research will dominate the frontiers of organometallics for the next several decades.…”
Section: Llnked-cage and Multidecker Complexesmentioning
confidence: 99%
“…Such studies, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] including those leading to peralkylation, perhydroxylation, or perhalogenation, continue to be of significant interest as the persubstitued borane or carborane clusters bear potential applicability in several areas as targets for anti tumor activity [22], weekly coordinating anion [23], components of radioimaging reagent [24], space-controlling drug component, [25]. Further, derivative chemistry has been shown to be crucial in some instances, e.g., modification of the reactivity of carborane fragments such that multiple stacking reactions are possible [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The demonstration of a useful synthesis of apically functionalized small metallacarboranes completes an armory of synthetic tools developed in our group in recent years, 3b,c, by which one can tailor such compounds via the introduction of functional groups at any boron or cage carbon vertex and by selection of the metal and metal-bound ligands. We envision the B(7)-derivatized complexes as precursors to a new class of small-metallacarborane linked systems that are connected via the apex boron atoms.…”
Section: Discussionmentioning
confidence: 87%
“…Much has been accomplished in the derivatization of large (12- and 13-vertex) metallacarboranes over a 30-year period, led by the pioneering work of Hawthorne, Zakharkin, Stone, and others considerable effort in our laboratory has been directed toward finding efficient methods for introducing organic and inorganic substituents at boron, carbon, and metal locations on the cage framework and for effecting direct cage-to-cage linkage . Such reactions are indispensable to any serious attempt at designed synthesis of metallacarborane-based electronic materials or catalysts.…”
Section: Introductionmentioning
confidence: 99%